Optimalisasi Media Sosial untuk Pemasaran Produk UMKM Kerupuk Mang Ujang di Salama Kota Bima - Purnama, Ita; Molita, Molita; Afrianingsih, Nur; Jannah, Miftahul (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
In the digital era, social media has become one of the effective and efficient marketing tools to increase product sales, especially for Micro, Small, and Medium Enterprises (MSMEs). This study aims to identify the role of social media in the marketing strategy of MSME products of Mang Ujang located in Salama, Bima City. The method used is a survey and direct training for MSME owners and employees. This activity includes product packaging training, labeling, and the use of various social media platforms such as WhatsApp, Facebook, Instagram, and TikTok for promotion. The results of the training showed an increase in MSME actors' understanding of digital marketing, which contributed to increasing brand awareness and product sales potential. In conclusion, social media can be a strategic tool for sustainable MSME business development amidst the challenges of the digital era.